Fence Bender " Mesin Pembentukan Logam Dengan Teknologi Bending" Sebagai Solusi Peningkatan K3 dan Efisiensi Produktivitas Home Industri Tralis di Kawasan Ngingas - Sidoarjo - Widodo, Buyung Prasetyo; Putra Dhewa, Ryantha Bagus; Alkaromi, Ilham; Raharjo, Dimas Afiyanto (Program Kreativitas Mahasiswa - Teknologi, 2014)
In small industry, trellis craftsmen have variety of stages in production process of trellis. They had only manually equipment to create a profile of fence. By using this manual process, it tends to increase operation cost and variety of quality of trellis fence. UD Jaya Makmur is a representative of trellis craftsmen who use manual equipment to produce trellis fences and other bar fences. Based on the background and the needs of this small fences industry, the fence bender machine has been built through Student Creativity Programme (PKM-T) which held by DIKTI. The process starting with exploring the machine design, then the proposed design had been analysed. After final calculation, the construction of fence bender machine was started, including profiling technology and automation. As the result, Fence Bender Machine has specification: Electric Motor 2 HP (Horse Power), Gearbox 1:60, Steel as material holder and can bend plate with 5 mm thickness. The machine was equipped by Holder/Bend Tool for bending or profiling. By comparing with manual production process, the fence bender can produce higher quality of trellis fence and better efficiency, because the machine can produce more fences and lower production cost. The production capacity of the machine was 240 products/hour for elbow profiles and 120 products/hour for circular profiles.Keywords: Fence Bender, Plate, Trellis.